Absorption and cutaneous deposition of yellow pigment in male and female broilers in response to different levels of xanthophylls from Tagetes erecta - Tepox-Pérez, MA; Fuente-Martínez, B; Hernández-Velasco, X; Quiroz-Pesina, M; Ávila-González, E; Téllez, G (Austral Journal of Veterinary Sciences, 2017)
To determine the saturation point of absorption and cutaneous deposition of yellow xanthophylls (XA) in broilers, two hundred and sixteen Ross 308 chickens (108 males and 108 females) were sorted by sex and randomly assigned to 6 dietary treatments containing 6 replications of 6 birds each. Treatments consisted of increasing levels of xanthophylls from Aztec marigold flower (Tagetes erecta) (65, 92, 119, 146, 173, and 200 ppm). Weight gain, feed consumption, and feed conversion were measured weekly. Plasma pigment levels and skin yellowness in live birds were measured twice per week. Growth performance was analysed through ANOVA for a 6X2 factorial arrangement, where the first factor was the XA adding at six levels, and the second factor was sex at two levels. Pigment plasma concentration and skin yellowness were fitted into a multiple linear regression model. Results indicated that the highest levels of plasma xanthophylls and skin yellowness were found after 28 d of feeding. Skin yellowness increased by 2.24 b* for every d of xanthophylls consumption. In the females, skin yellowness was 1.35 b* higher than in the males. Increasing dietary xanthophylls by 10 ppm was reflected in 0.83 b* of increase in skin yellowness.